Núcleo de Estudos Filosóficos sobre Gênero: uma experiência na Educação Básica - Costa, Dayane Evellin de Sousa (2020)
The idea of creating a group of philosophical studies on Gender in a basic education level arose through the perception of a reality that incorporates the dominant social practice which ignores the diversity of individuals. Once the philosophical knowledge is a possibility of reflection that provides young people with emancipatory thinking, this project deals with the creation of a Center for studies on gender seeking to leave the place of silence where such themes and individuals are found. Its development took place at the EEEP Presidente Roosevelt, a high school, full-time and professional education institution, a modality in the state of Ceará. The school is located in its capital, Fortaleza. In order for this experience to be feasible, we started by thinking about the role of Philosophy and Gender teaching in school, as well as understanding the perspective of an education focused on human rights, which is scrutinized in the first part of this text. Then, the perspectives of Beauvoir (2009), Foucault (2005) and Butler (2017) are presented as the basis that enabled the understanding and planning of this research. The methodology was based on action research, highlighting an interaction between the researcher and the group, at the same time that it fosters the engagement of research participants in claims, decisions, and actions. The years to be analyzed are 2018 and 2019. The Center meetings were based on readings, questionings and action-oriented planning aimed at the school community, which is detailed in the section four of this work. In order to figure out how this space gained meaning in its reflections, as well as its perceptions about the impacts it had on school experience, interviews with its members were carried out. When analyzing the replies, it is possible to perceive a critical understanding of the themes approached in the meetings, the overcoming of prejudices, and philosophical reading closeness. Finally, the external developments of the Center were evaluated, such as the development of scientific research initiation at the level of High School focused on such issues and how the experiences of the study group contributed to the planning of Philosophy activities in the classroom.